Clinical Instructor Training Using One Minute Preceptor (OMP) Guidance Method In Rsud Argamakmur North Bengkulu - Pebriani, Emi; Yuniarti, Pipi; Ramlis, Ravika (Universitas Dehasen Bengkulu, 2024)
The competence of professional nurses is measured through competency tests organized by the Ministry of Research, Technology and Higher Education (Kemenristek Dikti, 2015). But until now, there are still many problems encountered in nurse human resources in achieving competency test graduation well. Clinical learning determines the quality of nursing students' learning outcomes. Thus, preceptors can be said to be the embodiment of the implementation of the nursing education curriculum provided by clinical supervisors and can be a provision for students to apply knowledge based on their competencies. The lack of interaction time between preceptors and students can be caused by the workload of preceptors. Seeing the limitations and duties of preceptors, a clinical guidance method is needed that can overcome these problems. The One Minute Preceptor (OMP) guidance method is an effective guidance method that can be used in limited time (Fagundes et al., 2020). This clinical guidance method is a method that is not too complicated and is considered right on target to overcome the problem of limited time owned by preceptors (Seki et al., 2016). So it is necessary to organize a better learning system. This study aims to improve the ability of preceptors to educate students in providing safe nursing care. The type of research is quantitative with a pre-post test quasi experiment design. The sample in this study consisted of 37 preceptors. Academic Preceptor 11 people, Clinical Preceptor 26 people. Sampling with total sampling. The results showed that most of the preceptors were female, aged late adulthood (36-45 years), most had a Ners education and had been preceptors for 1-5 years. The mean post test scores of knowledge, attitudes, skills and cumulative preceptors were higher than the pre-test scores. This study shows that clinical instructors need to be equipped with understanding and skills in their implementation in guiding students. It is expected that preceptors can apply the One Minute Preceptor (OMP) guidance method in nursing practice